Analisis Pengaruh Return On Equity dan Non Performing Loan Terhadap Harga Saham pada PT. Bank Tabungan Negara Tbk. - Suryani, Suryani; M. Rimawan; Muniarty, Puji (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to examine: 1) The effect of Return on Equity (ROE) on the stock price of PT Bank Tabungan Negara Tbk; 2) The effect of Non-Performing Loans (NPL) on the stock price of PT Bank Tabungan Negara Tbk; and 3) The combined effect of Return on Equity (ROE) and Non-Performing Loans (NPL) on the stock price of PT Bank Tabungan Negara Tbk.This is an associative (causal) study using a quantitative approach. The data used in this research is secondary data in the form of financial reports, including net income, total equity, non-performing loans, total credit, and stock prices of PT Bank Tabungan Negara Tbk over a 10-year period from 2014 to 2023. Data collection techniques include documentation and literature study.The data analysis techniques employed in this research are: classical assumption tests consisting of normality test, multicollinearity test, heteroscedasticity test, and autocorrelation test; multiple linear regression analysis; correlation and determination coefficients; hypothesis testing; and model feasibility test.The results show that: 1). Return on Equity (ROE) does not have a significant partial effect on the stock price of PT Bank Tabungan Negara Tbk; 2). Non-Performing Loans (NPL) have a significant partial effect on the stock price of PT Bank Tabungan Negara Tbk; 3). Return on Equity (ROE) and Non-Performing Loans (NPL) do not have a significant simultaneous effect on the stock price of PT Bank Tabungan Negara Tbk.